2021
DOI: 10.1039/d1py00013f
|View full text |Cite
|
Sign up to set email alerts
|

An unexpected role of an extra phenolic hydroxyl on the chemical reactivity and bioactivity of catechol or gallol modified hyaluronic acid hydrogels

Abstract: We present here a new insight into the chemical reactivity and bioactivity of dopamine (DA) and gallic acid (GA) and their hyaluronic acid (HA) conjugates. Our data suggest that HA-GA...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(21 citation statements)
references
References 22 publications
0
21
0
Order By: Relevance
“…Catechol-functionalized polymers with metal ions have been proven to have rapid network formation, pH-tunable cross-linking, and self-healing activity. , The concentration of metal ions and pH can be used to precisely control the polymer network and their rheological properties . However, only a few studies have reported the application of GA–metal ion coordination chemistry to obtain printable biomaterial inks. , …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Catechol-functionalized polymers with metal ions have been proven to have rapid network formation, pH-tunable cross-linking, and self-healing activity. , The concentration of metal ions and pH can be used to precisely control the polymer network and their rheological properties . However, only a few studies have reported the application of GA–metal ion coordination chemistry to obtain printable biomaterial inks. , …”
Section: Introductionmentioning
confidence: 99%
“… 16 However, only a few studies have reported the application of GA–metal ion coordination chemistry to obtain printable biomaterial inks. 17 , 19 21 …”
Section: Introductionmentioning
confidence: 99%
“…Both these approaches are inefficient, rendering a poor coupling yield. To circumvent this we modified the carboxylate residues of GA to a hydrazide derivative as they are known to undergo proficient EDC coupling owing to a lower pK a of hydrazides over amines [35] . To achieve this we first transformed the carboxylate groups of GA to methyl ester followed by nucleophilic displacement with aqueous hydrazine (80% solution) to obtain GA-hydrazide in quantitative yields.…”
Section: Resultsmentioning
confidence: 99%
“…The hydrazide derivative of GA was characterized by 1 H and 13 C NMR spectroscopy (Figure S2 and S3 in SI). We have recently shown that compared to hydrogels obtained by NaIO 4 oxidation of dopamine conjugated HA, the hydrogel obtained by GA functionalized HA displayed faster oxidation at physiological pH and possess higher tissue adhesive properties [35] . In this study, the GA functionalized HA was grafted with carbodihydrazide (CDH) groups as a biorthogonal moiety that facilitates covalent crosslinking reaction with aldehyde functionalized HA derivative.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation